2011
DOI: 10.1111/j.1365-2141.2011.08703.x
|View full text |Cite
|
Sign up to set email alerts
|

A steroid‐independent regimen of bortezomib, liposomal doxorubicin and thalidomide demonstrate high response rates in newly diagnosed multiple myeloma patients

Abstract: Novel agents have provided new a foundation for multiple myeloma therapies. When combined with other anti-myeloma agents, these compounds significantly enhance clinical efficacy. High-dose steroids are frequently used in anti-myeloma combination regimens; however, the doses employed are often poorly tolerated, especially in patients with concurrent comorbid conditions. We hypothesized that a steroid-independent combination regimen could be developed without significant compromise of efficacy. The availability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Upon treatment with the VTD combination therapy, a decreased white blood cell count, hemoglobin level and platelet count, and gastrointestinal symptoms were the most common side effects in both groups, but these were not severe in the present study. These data were consistent with previous studies (22,23) and presented additional information about the scBor severity as part of a VTD combination therapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Upon treatment with the VTD combination therapy, a decreased white blood cell count, hemoglobin level and platelet count, and gastrointestinal symptoms were the most common side effects in both groups, but these were not severe in the present study. These data were consistent with previous studies (22,23) and presented additional information about the scBor severity as part of a VTD combination therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Detailed information with regard to other side effects of bortezomib have been sufficiently documented whether this is administered independently or as part of a combination therapy (18)(19)(20)(21)(22)(23). Upon treatment with the VTD combination therapy, a decreased white blood cell count, hemoglobin level and platelet count, and gastrointestinal symptoms were the most common side effects in both groups, but these were not severe in the present study.…”
Section: Discussionmentioning
confidence: 55%
“…Along with reduction in the severity of sensory neuropathy, the overall toxicity profile was manageable and no treatment associated deaths. 83 The promising results of such steroid-free regimens need further phase III verification for their clinical efficacy and relatively low toxicity.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…17 Other trial was shown comparable results of treatment with bortezomib, pegylated doxorubicin and thalidomide combination with 78% ORR, of which 35% achieved CR + nCR. The overall toxicity was manageable without treatment associated death.…”
Section: Clinical Evidences On Bortezomibmentioning
confidence: 89%